Congenital Bilateral Sporadic Aniridia: Review of Management - Caroline O Adeoti; Adeyinka A Afolabi; Adebimpe O Ashaye; Adenike O Adeoye (Medical Science: Trends and Innovations Vol. 2, 2025)
Purpose: This is to review the management modalities and report a rare case of bilateral sporadic aniridia in an African child. Presentation: A case of bilateral sporadic aniridia with horizontal nystagmus, cataract, optic disc and fovea hypoplasia in a 5-year-old female patient was reported. She was managed conservatively. Various modalities of treatment with their limitations were reviewed. Conclusion: Congenital bilateral aniridia is not generally common. As a result of the associated fibrotic nature, management is complex, may fail and may not be affordable or available in developing countries.